Thermal efficiency of nanofluid-based flat plate solar collector / Nang Khin Chaw Sint - Nang Khin, Chaw Sint (2018)
Liquid type flat plate solar collectors are mostly used in solar water heating (SWH) systems because of their simpler technology and lower cost. Current conventional flat plate solar collectors are relatively low in efficiency as compared to other types of solar collector because of their high heat losses. Therefore, flat plate solar collector is the key component needed to be improved to obtain a better SWH system performance. The application of nanofluid as a working fluid is one of the methods to enhance heat transfer rate of the solar collector, which can compensate the heat losses of the collector, in turn, can improve the collector efficiency. In this study, the application of a nanofluid-based flat plate solar collector for domestic solar water heating system, considering the weather condition of the Malaysian city of Kuala Lumpur, is proposed. The main objective of the present work is to perform a theoretical and experimental study to investigate the thermal efficiency of nanofluid-based flat plate solar collector located at University of Malaya, in Kuala Lumpur. The first phase of the present work examines the theoretical aspects of efficiency evaluation of the flat plate solar collector. The mathematical model was simplified for estimating the proposed collector efficiency. It was then used as part of a computer simulation program written in MATLAB language to determine the optimum tilt angle for the fixed-mount flat plate solar collector which maximises the incident solar radiation for a specified period and to estimate the optimum parameters of nanoparticle for preparation of nanofluid in order to maximise the collector efficiency. It was observed that the monthly optimum tilt angle for south-facing FPSC varies throughout the year, with its minimum value as -35˚ in June and maximum value as 41˚ in December. This result suggested that, if it is possible, the collector tilted angle should be adjusted once a month. Otherwise, the tilt angle should be changed at least twice a year, during the wet and dry seasons. Also, the results indicated that the collector efficiency increased with the increase in volume concentration of nanoparticles in nanofluid up to 0.5% of volume concentration. From this result, it can be stated that a 0.5% volume concentration is the optimal concentration for the collector nanofluid. The second phase is the experimental work, conducted under outdoor conditions, to verify the collector efficiency obtained from the simulation programme. The 0.5% CuO nanofluid (40 nm) was used as a working fluid and the ASHRAE standard was used for testing the thermal performance of nanofluid-based flat-plate solar collector. It was observed that the difference value between the calculated and experimental efficiency results obtained for the tested collector was less than 4%.